Adiponectin Paradox in Alzheimer's Disease; Relevance to Amyloidogenic Evolvability? - Waragai, Masaaki; Ho, Gilbert; Takamatsu, Yoshiki; Wada, Ryoko; Sugama, Shuei; Takenouchi, Takato; Masliah, Eliezer; Hashimoto, Makoto (Frontiers in Endocrinology, 2020)
Adiponectin (APN) is a benign adipokine that sensitizes the insulin receptor signaling, stimulates mitochondria biogenesis, and suppresses inflammation. By virtue of these beneficial properties, APN may be protective for metabolic disorders, including obesity and type II diabetes mellitus. Since these diseases are associated with hypoadiponectinemia, it is suggested that loss of function of APN might be involved. In contrast, despite beneficial properties for cardiovascular cells, APN is detrimental in other diseases, including chronic heart failure (CHF) and chronic kidney disease (CKD). Notably, such an APN paradox might also be applicable to neurodegeneration. Although APN is neuroprotective in various experimental systems, a recent prospective cohort study showed that APN was associated with the severity of amyloid deposits and cognitive deficits in elderly. Furthermore, Alzheimer’s disease (AD) was associated with hyperadiponectinemia in many studies. Moreover, APN was sequestered by phospho-tau into the neurofibrillary tangle in the postmortem AD brains. Collectively, these results suggest that APN might increase the risk of AD. In this context, the main objective of the present study is to elucidate the mechanism of the APN paradox in AD. Hypothetically, APN might be involved in the stimulation of the amyloidogenic evolvability in reproductive stage, which may later manifest as AD through an antagonistic pleiotropy mechanism in aging. Given the accumulating evidence that AD and CHF are mechanistically overlapped, it is further proposed that the APN paradox of AD might be converged with those of other diseases, such as CHF and CKD.